(untitled) (International Journal of Engineering and Computer Science, 2015)
Security is often vital in knowledge networks; however it’s significantly crucial in wireless networks like LTE. One in all the distinctive challenges of fourth-generation technology is the way to shut a security gap through that one compromised or malicious device will jeopardize a whole mobile network due to the open nature of these networks. To satisfy this challenge, relinquishing key management within the 3GPP LTE/SAE has been designed to nullify any vulnerable keys and as a result detach tainted network devices. Though periodic updates of the PGP key are Associate in Nursing integral a part of relinquishing key management, our work here emphasizes however essential these updates or to minimizing the result of asynchrony attacks that, as of now, can’t be effectively prevented. The main contribution, however, is to explore however network operators will verify for themselves Associate in Nursing best interval for updates that minimizes the communication load they impose ,whereas protective for the protection of user mobility. Our rational and simulation consideration indicate the impact of the key update interval on such performance criteria as constellation and user quality once victimization RSA and PGP.